Reasons and psychological causes. - Davis, Wayne (Philosophical Studies, 2005)
The causal theory of reasons holds that acting for a reason entails that the agent’s action was caused by his or her beliefs and desires. While Donald Davidson (1963) and others effectively silenced the first objections to the theory, a new round has emerged. The most important recent attack is presented by Jonathan Dancy inPractical Reality(2000) and subsequent work. This paper will defend the causal theory against Dancy and others, including Schueler (1995), Stoutland (1999, 2001), and Ginet (2002).Dancy observes that our reasons are neither psychological states nor causes, and that our reasons can be both motivating and normative. I argue that these observations are fully compatible with the causal theory. According to the reductive version I develop for both cognitive and optative reasons, what it is for an action to be done for a reason is for certain beliefs and desires to cause the action in a particular way. Our reasons for action are the objects of some of those beliefs and desires. The causal process has two stages. This theory explains not only Dancy’s observations, but also many other facts about reasons that alternative theories leave unexplained. I argue against Schueler and others that the non-appetitive desires entailed by acting for reasons are no less distinct and independent causal factors than the beliefs entailed. I go on to rebut arguments that the relation between psychological states and actions cannot be causal because it is non-empirical, rational, normative, or non-deterministic, and that explanations in terms of psychological causes are incompatible with explanations in terms of reasons.I make no claim here about the precise adequacy of the theoretical definitions I present. My goal is to show that a systematic theory along these lines is the most promising and fruitful approach to understanding an important aspect of human nature.